Bending Collapse Of Rectangular Section Tubes In Relation To The Bus Roll Over Problem - Kecman, Dušan (Cranfield University, 1979)
The thesis is concerned with the theoretical determination of the overall and local effects on the collapse behaviour of bus structures in a roll over situation. The aim is to enable an early selection of structural components, so that the finished body can absorb enough energy and preserve sufficient strength to meet the roll over safety requirements. Chapter 1 gives an introduction into the bus roll over problem, discusses the present safety legislation and reveals that there is very little information on the performance of buses in real accidents and that no collapse analysis of the complete structure or bending collapse of its details had been undertaken. The investigation into 21 bus roll over accidents, summarised in Chapter 2, showed that structural safety relies on both the overall collapse modes and hinge properties. Theoretical determination of the overall collapse mechanism and maximum strength of a typical British coach is carried out in Chapter 3 using the CRASHD collapse program. Some peculiarities of the finite element modelling are demonstrated and the analysis indicates that the collapse mechanism can be controlled by careful selection of various structural components. Chapter 4 emphasises the importance of a better understanding of the hinge behaviour in vehicle structures. Bending collapse of rectangular section tubes is investigated in Chapter 5 for hinge rotation angles up to 30-50 degrees. The analysis starts with determination of the maximum strength of sections which may buckle within elastic range. Repeatability of local collapse mechanisms enabled the definition of the appropriate theoretical model. Kinematic theorem of the limit analysis is then applied to derive the formula for the hinge moment-rotation curve. Particular attention is paid to the selection of the appropriate material properties. The agreement with experimental evidence (Chapter 6) was very good for the complete range of tubes tested. This range includes practically all the standard sections that are used in the general structural design. The theory is used in Chapter 7 to optimise sections from the safety point of view and, in combination with the CRASHD program, to predict the collapse behaviour of beams, bus rings and complete structure entirely on the theoretical basis. Static and dynamic tests of bus rings gave good agreement with theory. The practical aspects of the work have been emphasised throughout the thesis. Detailed explanation of all the major decisions has increased the volume of the text, but the author believes that this will prove useful for practicing engineers. People interested in essentials only are referred to Chapter 8 where all the most important conclusions are given.